الأمان الوظيفي لأعضاء هيئة التدريس الأجانب بالجامعات الحكومية السعودية وتأثيره على أدائهم الوظيفي بالتطبيق على أعضاء هيئة التدريس الأجانب جامعة الأمام محمد بن سعود الاسلامية - طلب حسن, احمد عبد الناصر (جامعة الوادي - University of Eloued, 2024)
This study aims to identify the reality of the impact of job security for foreign faculty members in Saudi public universities and its impact on their job performance. To achieve the objectives of the study, the researcher used the questionnaire as the main tool for the study, as it contained (36) items related to job security in its social and political dimensions and the extent of its impact on the dimensions of job security. (Teaching, scientific production, community participation). The study concluded that job security among foreign faculty members in Saudi universities fluctuated in arithmetic averages between high, medium, and poor, which indicates fluctuations in job security among foreign faculty members.
Job security for foreign faculty members in Saudi public universities and its impact on their job performance as applied to foreign faculty members at Imam Muhammad bin Saud Islamic University
مقال
Keywords: الاداء الاكاديمي ; جامعة الامام محمد ; الامان ال ; ظيفي; Job security; academic performance; Imam Muhammad bin Saud Islamic University